Notes on the taxonomy of some glassfrogs from the andes of Peru and Ecuador (Amphibia: Centrolenidae) - Cisneros-Heredia, Diego (2014)
We present new information on several species of centrolenid frogs from Ecuador and Peru that justify the placement of Centrolene fernandoi Duellman and Schulte as a junior synonym of Centrolenella audax Lynch and Duellman; Centrolenella puyoensis Flores & McDiarmid as a synonym of Centrolenella mariae Duellman & Toft; and Cochranella tangarana Du-ellman & Schulte as a synonym of Cochranella saxiscandens Duellman & Schulte.